Case report: Incidentally discovered case of pheochromocytoma as a cause of long COVID-19 syndrome - Ziegler, Christian G.; Riediger, Carina; Gruber, Matthias; Kunath, Carola; Ullrich, Martin; Pietzsch, Jens; Nölting, Svenja; Siepmann, Timo; Bornstein, Stefan R.; Remde, Hanna; Constantinescu, Georgiana (Frontiers in Endocrinology, 2022)
Pheochromocytomas (PCC) are rare but potentially lethal tumors that arise from the adrenal medulla. Clinical suspicion and diagnosis of PCC can be challenging due to the non-specific nature of signs and symptoms. In many patients infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) could lead to long-term symptoms including fatigue, headaches, and cognitive dysfunction. Here, we present the case of a patient incidentally diagnosed with PCC after imaging was performed due to persisting complaints after COVID-19 infection. A 37-year-old male was referred to our center because of a right-sided inhomogenous adrenal mass, incidentally found during a computed tomographic scan of the thorax performed due to cough and dyspnea that persisted after COVID-19 infection. Other complaints included profuse sweating, dizziness, exhaustion with chronic fatigue and concentration difficulties. The patient had no history of hypertension, office blood pressure was normal and 24-hour ambulatory blood pressure monitoring confirmed normotension, but with absence of nocturnal dipping. Plasma normetanephrine was 5.7-fold above the upper limit (UL) of reference intervals (738 pg/ml, UL=129pg/ml), whereas plasma metanephrine and methoxytyramine were normal at 30pg/ml (UL=84pg/ml) and <4pg/ml (UL=16pg/ml), respectively. Preoperative preparation with phenoxybenzamine was initiated and a 4 cm tumor was surgically resected. Profuse sweating as well as the dizziness resolved after adrenalectomy pointing towards PCC and not COVID-19 associated patient concerns. Altogether, this case illustrates the difficulties in recognizing the possibility of PCC due to the non-specific nature of signs and symptoms of the tumor, which in this case did not include hypertension and coincided with some of the symptoms of long COVID-19.